2010
DOI: 10.1051/0004-6361/200913800
|View full text |Cite
|
Sign up to set email alerts
|

New Herbig Ae/Be stars confirmed via high-resolution optical spectroscopy

Abstract: We present FEROS high-resolution (R ∼ 45 000) optical spectroscopy of 34 Herbig Ae/Be star candidates with previously unknown or poorly constrained spectral types. Within the sample, 16 sources are positionally coincident with nearby (d < 250 pc) star-forming regions (SFRs). All the candidates have reported infrared excess. We determine the spectral type and luminosity class of the sources, derive their radial and projected rotational velocities, and constrain their distances employing spectroscopic parallaxes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 38 publications
(58 reference statements)
5
54
0
Order By: Relevance
“…These values rule out a post-AGB classification and make the star a candidate LBV. Subsequent studies confirmed the spectral classification as a B5-B9 star with emission lines that show P Cyg profiles (Carmona et al 2010) and Brackett emission lines in the near-IR without detectable CO bands (Venkata Raman & Anandarao 2008).…”
Section: Mwc 930mentioning
confidence: 79%
“…These values rule out a post-AGB classification and make the star a candidate LBV. Subsequent studies confirmed the spectral classification as a B5-B9 star with emission lines that show P Cyg profiles (Carmona et al 2010) and Brackett emission lines in the near-IR without detectable CO bands (Venkata Raman & Anandarao 2008).…”
Section: Mwc 930mentioning
confidence: 79%
“…• EPIC 204399980 (HIP 79476 = HD 145718) has been studied spectroscopically in some detail by Carmona et al (2010). The spectrum displays an inverse P Cygni Hα profile, presumably a result of accretion, confirming the Herbig Ae nature of this star.…”
Section: Spectroscopic Follow-upmentioning
confidence: 91%
“…On this basis we believe that our estimate of T spec eff =8100±300 K is sound. In passing, we note that our CAOS spectrum allows us to evaluate the possible multiplicity of EPIC 204399980, by comparing our determination of V rad =−7.4±6.4 km s −1 with Carmona et al (2010)'s V rad =0±3 km s −1 . The two values agree within ∼ 1 σ, hence we conclude that at least with present data, there is no evidence of multiplicity for this star.…”
Section: Caos Spectramentioning
confidence: 99%
“…Where an appropriate synthetic spectrum was not available, we used a synthetic spectrum of similar spectral type as the star observed. For this purpose we used the interactive IDL-based software described in Carmona et al (2010). This tool allows the synthetic and target spectra to be displayed, and to calculate the radial velocity of the observed spectrum using the cross-correlation technique.…”
Section: A21 Determination Of the Stellar Radial Velocity From Uvementioning
confidence: 99%